Literature Review on Strategies for Improving Language Skills for Indonesian Language for Foreign Speakers (BIPA) - Islahuddin, Islahuddin; Tawandorloh, Ku-Ares; Menjamin, Sumaiyah; Waeno, Mahamadaree (PUSAKA: Journal of Educational Review, 2025)
Strategies to improve language skills for teaching Indonesian Language for Foreign Speakers (BIPA) can be implemented through various effective and innovative learning approaches. This research aims to identify and analyze the effective strategy for enhancing language skills for Indonesian Language for Foreign Speakers (BIPA) through the Systematic Literature Review (SLR) method. SLR is chosen to identify, evaluate, and interpret all relevant studies. The researcher utilizes the Google Scholar database as the main source to collect relevant literature from 2020 to 2024. The review results show that a combination of communicative approaches, the use of technological media, project-based learning, and direct interaction with native speakers are effective strategies for developing Indonesian language skills for foreign speakers. These findings are expected to contribute to developing more effective and efficient BIPA programs.